Costs and usage of healthcare services before and after open bariatric surgery - Kelles, Silvana Marcia Bruschi (2011)
CONTEXT AND OBJECTIVE: Morbidly obese individuals are major consumers of healthcare services, with high associated costs. Bariatric surgery is an alternative for improving these individuals’ comorbidities. There are no studies comparing costs before and after bariatric surgery in Brazil. The aim here was to analyze results relating to healthcare usage and direct costs among morbidly obese patients undergoing bariatric surgery. DESIGN AND SETTING: Historical cohort study on patients receiving healthcare through a private health plan in Belo Horizonte, Minas Gerais. METHODS: All healthcare services and their associated costs were included in the analysis: hospitalization, hospital stay, elective outpatient consultations, emergency service usage and examinations. The analyses were treated as total when including the whole years before and after surgery, or partial when excluding the three-month periods adjacent to the operation. RESULTS: For 382 obese patients who underwent open bariatric operations, there were 53 hospitalizations one year before and 95 one year after surgery (P = 0.013). Gastrointestinal complications were the main indications for post-procedure hospitalizations. The partial average cost almost doubled after the operation (US$ 391.96 versus US$ 678.31). In subgroup analysis, the costs from patients with gastrointestinal complications were almost four times greater after bariatric surgery. Even in the subgroup without complications, the partial average cost remained significantly higher. CONCLUSION: Although bariatric surgery is the only path towards sustained weight loss for morbidly obese patients, the direct costs over the first year after the procedure are greater. Further studies, with longer follow-up, might elucidate whether long-term reversal of this trend would occur.